Hot-dip galvanizing of steel structures - Kuklík, Vlastimil; Kudláček, Jan (Butterworth-Heinemann, imprint of Elsevier, 2016)
This publication contains practical information that is useful for both researchers in hot-dip galvanising and engineers, designers, and inspectors. It draws from the empirical experience and research of the authors, complementing the current state of knowledge of morphological variations of the coating and causes of coating delamination.